PENGEMBANGAN SISTEM INFORMASI COMICREADER MENGGUNAKAN KERANGKA KERJA YII - Sabila Rusyda; Aristoteles Aristoteles; Dwi Sakethi (Jurnal Komputasi, 2016)
Comic is a general term used to denote the phenomenon of images that is put together in sequence and placed side by side.  It is usually available in the form of physical book, but in order to follow the development of digital technology, digital comic was born.  ComicReader is an application that is created to digitally distribute and read comics.  This application uses Yii as the framework.  Yii is a PHP based framework that uses the MVC architectural pattern.Keywords: comic, framework, yii.